Exploring Infinite Groups in This Thesis Was to Discover Homomorphic Images of Non-Abelian Finite Simple Groups - Khantwal, Deepak (International Journal of Control and Automation, 2018)
To create non-abelian finite simple groups as homomorphic pictures, this thesis explores infinite groups. These semidirect products, or progenitors, are infinite groups. Researched ancestors x of x permutations: x